Reconstruction of Postburn Full Facial Deformities With an Integrated Method. Issue 5 (July 2016) - Li, Qing Feng; ,; Zan, Tao; Li, Haizhou; Gu, Bin; Liu, Kai; Xie, Feng; Xie, Yun; Herrler, Tanja; Tremp, Mathias; Zhou, Shuangbai; Huang, Xiaolu; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Background: The face is one of the most important regions of the human body and contains complicated and delicate features that define the identity of a person. Treatment for extensive facial deformities requires resurfacing of the extensive skin defects and restoring the missing features. To date, it remains a major challenge to the reconstructive surgeons. Methods: The authors reviewed their patients of Type III and Type IV facial deformities to introduce an integrated method for total facial reconstruction. The entire management included flap prefabrication, skin over-expansion, bone marrow mononuclear cell transplantation, and multistaged revisions to reshape the face contours. The treatment details and postoperative results were presented. Aesthetic and functional status scores were independently evaluated to analyze the effectiveness of this intervention. Results: Forty-two patients with severe facial deformities were included. In 2 patients of total face reconstruction, bone marrow mononuclear cell transplantation was conducted. Each patient had facial reconstruction with a prefabricated flap (range 23 × 18–32 × 30 cm 2 ) that resurfaced the entire defect. Tip necrosis occurred in 2 patients. The aesthetic and functional status scores were statistically improved. Good skin compliance, normal contours, and emotional expression were noted. Conclusions: The integrated method is a reliable and excellent option for extensive facial deformities involving both central and peripheral facial units while avoiding multiflap reconstructions. It creates a desirable coverage with minimal scars, which are both important for a "perceived normal" face.